Understanding and supporting the academic needs of students with ADHD - Hagaman, Jessica L.; Casey, Kathryn J. (Special Education, 2016)
The National Survey of Children’s Health, conducted in 2011-12, reported one in ten school aged children received an ADHD diagnosis, an increase of 42% between 2003 and 2011 (Visser et al., 2013). This increase is troubling because ADHD is known to have an adverse impact on behavioral functioning, particularly in school settings, which negatively impact multiple aspects of a student’s life. Common problems include maladaptive social interactions and interpersonal relationships (Litner, 2003; Barkley, Fischer, Smallish, & Fletcher, 2004), lower achievement scores, and higher grade retention and dropout rates when compared to children without disabilities (Birchwood & Daley, 2012; Barkley, 2015). Considering the increasing prevalence and negative impact of this diagnosis, it is imperative that teachers understand the characteristics, treatments, interventions, and implications of this disorder. The purpose of this article is to provide information and guidance to teachers on the academic needs of children and adolescents with ADHD.
Keywords: ADHD; academics; executive functions